El cumplimiento de las funciones y deberes legales de los servidores policiales como causa de exclusión de la antijuridicidad: análisis del artículo 30.1 del COIP - Vallejos Yépez, Jonny Alexander (2024)
The purpose of this work is to expose the reader to the legal figure of compliance with a legal duty, provided for in Art 30.1 of the Ecuadorian Comprehensive Criminal Organic Code, within the theory of crime this figure acts as a cause of exclusion of illegality, That is to say, it allows the police officer to justify harmful conduct, as long as his actions comply with each of the requirements that the norm demands. The importance of this work lies in the fact that the insecurity and crime rates in Ecuador have reached levels never seen in its history, so the work of police officers acquires greater relevance in the current context as they are the ones who by constitutional provision must face this problem, for this reason the general objective of the present investigation is to analyze the budgets that configure 'the fulfillment of legal duty' as a cause of the exclusion of illegality, this in order to establish the limits on which law enforcement agents must fit their actions, the objective was achieved through the application of the normativist method, which allowed us to review both the internal regulations and international instruments that contain the principles and guidelines for the correct actions of the agents in charge of enforcing the law. Additionally, through the application of the survey technique, it was possible to identify the level of knowledge on the part of the of police officers, where It was evident that police officers have knowledge of their legal duties. Added to this, there are also specific cases in which compliance with legal duty was applied, exempting the police officer from all types of criminal liability, fulfilling the purpose of which this legal figure was introduced in the criminal regulations.